Perkembangan dan Peranan Radio Berbasis Islam - Effendy, Erwan; Siregar, Elsa Adelia; Alwi, Hadad; Fitri, Putri Chairina (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
To carry out da'wah activities we can use many ways. For example, by using something that can only be heard, it's easy because it can be heard anywhere and carried anywhere via radio. In this day and age radio does not only function as a means of conveying news but radio now also functions as a means of entertainment and even as a means of communication, education and also now radio can be used as a means of preaching. As we know from the past until it has developed like now, radio is a medium that can only be heard, besides being easy, radio is also cheap for the community. Even though the development of the current television era has emerged, the role of radio in society is irreplaceable. Not a few parents and even teenagers who still use radio for daily entertainment. Keywords: Radio, television, preaching, society.